Java software solutions : - Lewis, John (Pearson/Addison Wesley, 2005)
This book takes an early object oriented approach to Java Embracing Java 5.0 topics, including the new standard Scanner class for simplified keyboard input and parsing, enumerated types, autoboxing, variable length parameter lists, the enhanced for loop, and generic types. This new edition has an earlier evolution of object concepts, developed in a way that capitalizes on the power of objects without overwhelming beginning programmers. It includes all new Java 5 topics, including Scanner class, enumerated types, autoboxing, variable length parameter lists, the enhanced for loop, and generic types. This is in depth coverage on GUI applications. This book is appropriate for beginning programmers who want to learn to program with Java as well as experienced programmers who want to add Java to their skill-set.